Socialization of Local Waste-Based Organic Fertilizer and Ultrasonic Solar-Powered Water Monitoring Sensors to Improve Food Security in Menganti Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service activity was carried out in Menganti Village, Glagah District, Lamongan Regency, with the aim of increasing community knowledge and skills in the application of environmentally friendly agricultural technology as a strategy to strengthen food security. A total of 35 participants consisting of members of farmer groups, housewives, and village youth participated in this activity. The implementation method included socialization, training in making organic fertilizer from goat manure, ash, and rice husks, and a demonstration of an automatic water level measuring device based on a solar-powered ultrasonic sensor. Evaluation was carried out through pre-tests and post-tests of knowledge and practical observations. The results of the analysis showed a significant increase in participant knowledge, from an average of 25.54 in the pre-test to 87.51 in the post-test (Δ = 61.97 points; t(34) = 37.06; p < 0.001; Cohen's d = 6.27). Participants also demonstrated skills in the practice of making organic fertilizer and a high interest in adopting water sensor technology. This activity has had a positive impact in raising public awareness about sustainable agriculture, reducing dependence on chemical fertilizers, and opening up opportunities to utilize renewable energy technologies for efficient water management. Therefore, this outreach can serve as a model for strengthening food security based on sustainable local innovation.